Conceptualizing student protest: An analysis of fire metaphors in al Jazeera Arabic’s discourse in pro-Palestine movements at Western universities - Nadiya Khairunnisa; Tajudin Nur; Fahmy Lukman (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: Following the Hamas attack on October 7, 2023, Israel's military attacks on Palestine have become increasingly brutal, sparking massive protests by students at Western universities. Al Jazeera plays a significant role in shaping public perception of this discourse. In its reporting, Al Jazeera frequently uses metaphors. The fire metaphor is among the most effective and is often used in various contexts. Aims: This research aims to examine the conceptual metaphor of fire in Al Jazeera Arabic's discourse on pro-Palestinian student protests at western universities and reveal its ideological functions. Methods: This research employed a qualitative descriptive method, with analysis grounded in conceptual metaphor theory (CMT) (Lakoff & Johnson, 2003). The data source was pro-Palestinian student protest discourse on Al Jazeera Arabic. Data analysis uses the metaphor identification procedure (MIP) by the Pragglejaz Group. Results: These findings reveal that Al Jazeera Arabic uses lexemes related to fire to conceptualize and frame pro-Palestinian student protests at Western universities. Among the thirteen lexemes found, ʔimtadda ‘spread’ (19 data), ʔintašara 'spread' (12 data), and šarārah 'spark' (12 data) appear most frequently to highlight the rapid escalation of the protest movement and its massive impact. The metaphorical mapping of all the lexemes found constructs the conceptual metaphor PROTEST IS FIRE, highlighting student action as a significant and impactful force like fire. Implications: The significance of this research lies in its contribution to expanding the understanding of how the fire metaphors is not only a linguistic feature but also a cognitive and ideological device for shaping public perceptions of pro-Palestinian protests.